Evaluation of stress distributions in peri-implant and periodontal bone tissues in 3- and 5-unit tooth and implant-supported fixed zirconia restorations by finite elements analysis - Guven, Sedat; Beydemir, Koksal; Dundar, Serkan; Eratilla, Veysel (Dental Investigations Society, 2015)
Objective: In this study, it is aimed to compare the distribution of stress on periodontal and peri-implant bone tissues in 3- and 5-unit-dental and implant-supported zirconia restorations using finite element analysis. Materials and Methods: Stress distribution formed in periodontal and peri-implant bone tissues as a result of chewing forces was analyzed in dental and implant-supported three-dimensional (3D) finite element models of zirconia restoration with 5-unit placed on the numbers of 43, 44, 45, 46, and 47 and with 3-unit placed on the number of 45, 46, and 47. Four different loading conditions were used. 200 N force was applied in 30° from the buccal inclination of number 43, 45, and 47 restorations separately and totally 850 N force was applied in 30° from the buccal inclination of whole restoration. The study was performed through static nonlinear analysis with the 3D finite element analysis method. Results: Stress accumulation in bone tissues in the tooth-supported model was found less than in implant-supported models. Stress accumulation was observed in the cervical portion of the implant in implant-supported models, and stress accumulation was observed surrounding bone of roots in tooth-supported models. The highest stress values were occurred in 5 unit implant-supported model in all loadings. Conclusion: In posterior restorations increased in the number of supported teeth and implant can reduce the destructive forces on periodontal and peri-implant bone tissues and may allow longer period retention of the restorations in the mouth. © 2015 European Journal of Dentistry.
Keywords: Finite element analysis; Implant-supported prosthesis; Peri-implant and periodontal bone; Tooth-supported prosthesis; Zirconia restorations